Insights of Nanoemulsion as a Drug Delivery System: An Overview of Current Trends and Applications - Elsewedy, Heba S. (Indian Journal of Pharmaceutical Education and Research, 2025)
The ability of nanoemulsion to improve the solubility, bioavailability and stability of weakly water-soluble drugs has emerged their roles as promising drug delivery systems. Nanoemulsion is advanced colloidal systems made up of nanometer-sized droplets (usually 20-200 nm) scattered in two immiscible liquids and stabilized by surfactant. It offers a flexible substrate for enclosing both hydrophobic and hydrophilic medications. Owing to the tiny droplet size, there is more surface area available for absorption and more precise distribution to particular tissues or cells. Accordingly, nanoemulsion has drawn a lot of attention in a variety of industries, including medicine, cosmetics, food and agriculture. Its application in medical field includes drug delivery, drug administration and vaccine formulation. Nevertheless their benefits, some concerns may represent obstacles that hinder their applications such as formulation complexity, stability issues and industrial production scale-up. To get beyond these hurdles and completely realize the potential of nanoemulsion in commercial and therapeutic applications, more research and innovation are needed.
Keywords: Nanoemulsion; Formulations; Characteristic; Drug delivery; Application.